Analisis Perencanaan Permintaan Customer untuk Produk Rear Fender di PT MI - Rifda Ilahy Rosihan; Murwan Widyantoro; Roberta Heni Anggit Tansiri; Fadil Triawan (Universitas Teuku Umar, 2023)
PT. MI is one of the companies engaged in the manufacturing sector. Rear Fender is a product that produce by PT. MI. The problems for this research is the difference between demand customer and orders which is too far resulting in the remaining stock, with the average of stock is 8,33%. Inventory cost can increase because of excess stock. This aims of the study is to find the best forecasting method for rear fender products. The forecasting method is Moving Average, Weighted Moving Average, and ARIMA. The forecasting method is depend on demand data plots. The result of demand data plots it horizontal plotting so the forecasting method is time series method. The best Forecast for rear fender products is the ARIMA with the ARIMA model (1,1,0). The ARIMA method was chosen because the MAPE values are 13.305, MAD 5435.45 and MSE 41988401 which are the smallest when compared to the 2 other time series forecasting methods.